Relationship between vastus medialis oblique angle, Lysholm score, isometric quadriceps strength, and Tegner score in anterior cruciate ligament reconstruction patients - dyah paramitha dewi, I Gusti Agung; Adhitya, I Putu Gde Surya Adhitya; Putra, I Putu Yudi Pramana (Kinetic and Physiotherapy Comprehensive, 2025)
Background: The anterior cruciate ligament (ACL) tear represents a serious sports injury in active individuals. While reconstruction seeks to restore knee stability and quadriceps strength, full recovery of the vastus medialis oblique (VMO) angle is frequently not achieved. This study aimed to investigating the relationship between the vastus medialis oblique angle (VMOA) and Lysholm score with quadriceps isometric strength and Tegner score in patients after ACLR. Methods: This research used a literature review method of seven relevant scientific journals published within the last 10 years (2015–2025). The literature was selected based on strict inclusion and exclusion criteria from reputable scientific databases. These include PubMed, Scopus, Google Scholar, and PEDro using the keyword "vastus medialis oblique," which is also a keyword for "vastus medialis," "Lysholm score," "quadriceps isometric," and "Tegner score." Results:  There waa a significant relationship between VMOA angles and isometric quadriceps strength and functional values of Lysholm and Tegner. Patients with VMOA angles within the ideal range and adequate quadriceps muscle strength generally showed better knee functional value and activity level. Rehabilitative interventions, such as the use of hybrid assistance limb (HAL) and electro muscle stimulation (EMS), have been shown to be effective in improving muscle strength and clinical scores. Conclusion: This study concluded that there was a significant relationship between VMOA angles, isometric quadriceps strength, and Lysholm and Tegner functional scores in patients after ACLR. The findings emphasize the importance of rehabilitation focusing on strengthening VMO and quadriceps muscles to improve knee stability and post-ACLR clinical outcomes.